Improvement of soil shear strength using glucomannan biopolymer for loose sand. Issue 1 (October 2021) - Lim, A; Iskandar, M R; Albrecht, Y
Abstract: Biopolymers are popularly known as environmentally friendly soil improvement materials that could substitute the use of cement, where considered might harm the environment. Glucomannan is a polysaccharide obtained from Iles-Iles ( Amorphophallus muelleri ) plant that is widely used as a gel and thickening agent. Glucomannan is soluble in both cold and warm water and when glucomannan is mixed with warm water, it will form a thick solution that would not be dissolved with cold water. In this study, Glucomannan was used as a stabilizer to enhance the mechanical properties of uniformly graded loose sand. An experimental study using the Direct Shear Test was conducted to obtain the shear strength parameters, such as cohesion and internal angle friction of the treated soil. The main mechanism is the gelation increase the cohesion of the sample significantly. In addition, the stabilizer mechanism was observed using a digital microscope where it proofs that translucent thin layers bond between particles in the treated soil.